Teachers' Perceptions of Using Pedagogic Content Knowledge Technology in the Teaching of Physical Education - Hanifah Fauziah; Dian Budiana; Helmi Firmansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Advancement in technology is something that cannot be avoided in human life. This research is descriptive research with mixed methods of sequential explanation. This design is carried out to explore a research phenomenon involving several data sources. This research aims to evaluate which parts are still obstacles for physical education teachers in using technology in physical education learning. The results of this study indicate differences in the TC domain (Technological Content) in the TC domain; there are differences in the average results of each group, followed by the post hoc test and the Tukey test. The average difference was found between the 1-7 year group and the 29-year-old group. 35 years old, the lowest average score in the group is 29-35 years old, and the highest is 22-28 old